2021
DOI: 10.1142/s0218348x21501206
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Sir Mathematical Model for Covid-19 Outbreak in Pakistan Under Fractal-Fractional Derivative

Abstract: There are still mathematical predictions in the fight against epidemics. Speedy expansion, ways and procedures for the pandemic control require early understanding when solutions with better computer-based mathematical modeling and prognosis are developed. Despite high uncertainty in each of these models, one of the important tools for public health management system is epidemiology models. The fractional order is shown to be more effective in modeling epidemic diseases, in relation to the memory effects. Nota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Nian et al (2021) proposed a SEIRD model with fractal propagation characteristics. After that, Ali et al (2021) study uses fractal fractal derivatives for the first time to model empirical data. However, few scholars have studied the propagation characteristics of epidemics from the perspective of effective fractal dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Nian et al (2021) proposed a SEIRD model with fractal propagation characteristics. After that, Ali et al (2021) study uses fractal fractal derivatives for the first time to model empirical data. However, few scholars have studied the propagation characteristics of epidemics from the perspective of effective fractal dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, nowadays the researchers are devoting their research work to the fractional-order COVID-19 mathematical models. A huge number of good research papers related to fractional-order COVID-19 mathematical models can be found in the literature, some of them are the following: Caputo fractional-order [ 46 , 47 ], Caputo–Fabrizio fractional-order [ 48 , 49 ], Atangana–Baleanu fractional-order [ 50 , 51 ], fuzzy fractional-order [ 52 , 53 ], fractal-fractional order [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al. [2] studied a SIR model to assess the dynamics of COVID 19 using fractals Fraction operator. By using power-law kernels and new applications, Akgul [3] described some advances in fractal fractional differential equations.…”
Section: Introductionmentioning
confidence: 99%